Use of Siberian mineral raw materials in the manufacture of self-glazing ceramic tile; Glass and Ceramics; Vol. 54, N 11-12 - Pogrebenkov V. M. (1997, 1997)
It is shown to be possible to manufacture self-glazing ceramic tile of satisfactory quality from the mineral raw materials available in the Siberian region and the soda-alkali effluent from a local petrochemical plant